Republic of the Marshall Islands : 2005 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of the Marshall Islands. (IMF Staff Country Reports; Country Report ;, 2006)
Real output growth of the Republic of the Marshall Islands appears to have slowed sharply in FY2003 and again in FY2004. The 2005 Article IV Consultation highlights that the economic activity has been hampered by delays in implementing an upgraded public works program and the closure of a large privately owned tuna processing plant. The fiscal position deteriorated in FY2004. This deterioration reflects, on the revenue side, a decline in grants aimed at infrastructure projects owing in part to delays in initiating projects, lower income tax collection, and volatility in nontax revenue.